Oscar Wilde`s novels "The picture of Dorian Gray" as an expression of the author`s disapproval of the hypocrisy of victorian society - Utíkalová, Monika (Univerzita Pardubice, 1998)
Cílem práce je obhájit názor, že novela Oscara Wildea "Obraz Doriana Graye" je výrazem autorova nesouhlasu s přetvářkou viktoriánské společnosti.
Keywords: Oscar Wilde; viktoriánská společnost